Bioaktivitas Ekstrak n-Heksana dan Alkaloida Kasar Kulit Batang Actinodaphne macrophylla (Blume) Nees var angustifolia Koord & Valeton - Rachmatiah, Tiah; Subaryanti, . (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
Bioactivies of n-hexane extract and crude alkaloid extract from stem bark of Actinodaphne macrophylla (Blume) Nees var angustifolia Coordinator. & Valeton (Lauraceae) have been investigated. The plants of Lauraceae family are known to contain active compounds such as alkaloids, lactones, fatty acids, terpenes and essential oils. Phytochemical screening of the bark exhibited that it contains triterpenoids, alkaloids and tannins. N-hexane extract was prepared by maceration and the crude alkaloid extract was prepared by maceration in dichloromethane after the powdered bark was previously moistened with 25% NH4OH. The bioactivity assays involved the test of toxicity against brine shrimp larvas (Artemia salina Leach), cytotoxicity against Murine P-388 cells and antimalarial against Plasmodium falciparum. The results indicated that n-hexane extract was active against shrimps larvas with LC50 value of 85.11 ppm, and against P.falciparum with IC50 values of 1.824 ppm, but inactive against Murine P-388 cells with IC50 values of 43.0 ppm, while the crude alkaloid extract was active against shrimp larvas with LC50 value of 36.31 ppm, against Murine P-388 cells with IC50 values of 5.2 m ppm, and against P.falcifarum with IC50 value of 0.1 ppm.Keywords : Lauraceae, Actinodaphne, bioactivity, alkaloids, extract.